CURVATURE OF SPACE AND TIME IN A STRONG GRAVITATIONAL FIELD - Akmalbek Qadamov Alisherovich (Ustozlar uchun, 2025)
Annotation: This article explores the curvature of space and time under the influence of strong gravitational fields as predicted by Einsteins general theory of relativity. We analyze how massive bodies distort the geometry of spacetime, especially in regions surrounding black holes and neutron stars. By reviewing key literature, applying mathematical modeling, and interpreting the consequences through astrophysical observations, the article outlines the theoretical and observable implications of spacetime curvature in extreme gravity environments.